The Effect of Motivation and Work Discipline on Employee Performance with Work Environment as a Moderating Variable in BPJS ketenagakerjaan in Medan Raya - Muhammad Imam Perdana; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
In this study, the researcher wants to see the direct and indirect influence between motivation variables, work discipline as an independent variable and organizational work environment as a moderation variable and employee performance as a bound variable. The type of research used is quantitative, this research was carried out at BPJS ketenagakerjaan Branches throughout Medan Raya which consisted of BPJS ketenagakerjaan Offices Medan City Branch, Medan Kisaran Branch, and Tanjung Morawa Branch. The population of this study is 82 employees and the sample used is the entire population using a saturated sampling technique. The data source used is the primary data source and data collection is carried out by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measuring tool. The results of the study are as follows: Work discipline has a negative and insignificant effect on employee performance with an original sample value of -0.226 and a P value of 0.170. Work motivation had a positive and significant effect on employee performance with an original sample value of 0.474 and a p value of 0.003. Work discipline has a positive and significant effect on employee performance through the work environment indirectly with the original sample result of 0.542 and p value 0.000. Work Motivation had a negative and insignificant effect on employee performance through the work environment indirectly with an original sample value of -0.164 and a p value of 0.033.